2019
DOI: 10.1111/cas.14187
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase Eph receptor A6 sensitizes glioma‐initiating cells towards bone morphogenetic protein‐induced apoptosis

Abstract: Bone morphogenetic protein (BMP) signaling plays important roles in glioblastoma multiforme (GBM), a lethal form of brain tumor. BMP reduces GBM tumorigenicity through its differentiation‐ and apoptosis‐inducing effects on glioma‐initiating cells (GIC). However, some GIC do not respond to the tumor suppressive effects of BMP. Using a phosphoreceptor tyrosine kinase array, we found that EPHA6 (erythropoietin‐producing hepatocellular carcinoma receptor A6) phosphorylation was regulated by BMP‐2 signaling in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…BMPs, e.g., BMP2/4/7, and their downstream signaling, type I receptor [ 26 , 27 ], have been found for their potential inhibitory roles in glioma tumorigenicity since 2006 [ 28 ]. However, after extensive investigations, although most of the studies have demonstrated their glioma-suppressor roles [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], accumulating data indicated that the BMPs effect on glioma development might be tumor phenotype-dependent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMPs, e.g., BMP2/4/7, and their downstream signaling, type I receptor [ 26 , 27 ], have been found for their potential inhibitory roles in glioma tumorigenicity since 2006 [ 28 ]. However, after extensive investigations, although most of the studies have demonstrated their glioma-suppressor roles [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], accumulating data indicated that the BMPs effect on glioma development might be tumor phenotype-dependent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, estrogen treatment increases the reduction of BMPRI [10]. Furthermore, expression of BMPRI or BMPRII exhibited significant loss in patients of poorly differentiated prostate cancer, renal cell carcinoma, urinary bladder cancer [5,11,12] and BMPRI expression frequently reduced and associated with poor survival in pancreatic cancer patients and inactivation of BMP signaling induces invasiveness of tumor [6] and BMP-2 induced apoptosis of glioma by induction of BMPRI [13]. However, other studies suggest that BMP signaling engaged in tumorigenesis and metastasis of tumors as tumor promotor.…”
Section: Introductionmentioning
confidence: 99%
“…Gremlin1, an extracellular antagonist of BMPs, is secreted by GICs and maintains their stem cell‐like properties by inhibiting endogenous BMP signaling [ 19 ]. We showed that, among the three BMP type I receptors expressed in GICs, ALK‐2 plays a major role in apoptosis regulation [ 20 ] and that cooperation with EphA6 tyrosine kinase receptor sensitizes some resistant GICs for BMP‐induced apoptosis [ 28 ]. However, because of the heterogeneity of glioblastoma cells, certain other BMP target molecules may also be critically involved in differentiation and apoptosis of GICs, and it remains to be elucidated how the stem cell‐like properties of GICs are regulated by BMPs.…”
Section: Introductionmentioning
confidence: 99%